A TECNOLOGIA DA INFORMAÇÃO COMO ELEMENTO DE MELHORIA DOS PROCESSOS FINANCEIROS DA PEQUENA E MÉDIA EMPRESA - Galdino, Clóvis Luiz (2008)
The complexity in which corporations operate nowadays is such that demands efficient information systems (ISs), which can be used as support to managers decision making, particularly in areas linked to Information Technology (IT) in the face of the new management paradigms the small and med ium size organizations (SMSOs) must confront. The broad objective of this paper is to evaluate the perception managers of Brazilian SMSOs have over the impact of the IT used as an element of improvement to financial processes in organizations. For this to be achieved it was developed and studied the following specific targets: to verify in which way IT is perceived as useful in SMSOs, particularly in standardized treasury financial automation and cash flow; to verify whether automation of financial routines using IT can help the decision making in such organizations; and to verify whether its use is seen as an strategic advantage. In the bibliographic research done, this paper presents concepts related to Competition, Small and Medium Size Organizations, Strategy and Competence Management. These concepts where found not only in the literature but in specialized press articles as well. At the empiric research done this paper aimed, in studying multiple cases in five different firms, to deepen the questions linked to managers perception on the IT applied over the financial proceedings introduced in the organizations run by them. The planning of the sample was done so to permit not only the individual analysis of each answering, but also the analysis of the organizations where they operate. The conclusions reached were: a) That managers perceive the IT application on financial routines and cash flow as vital once automation is necessary to maintenance and speeding up of the relationship processes with clients and suppliers; b) That IT can improve the structured decision making processes, particularly in decisions related to financial routines. Another aspect that becomes clear in the managers view is that the firm s dependence on the ISs increases as the firm grows and, therefore, with the amount of information managers have to deal with; c) That, in the managers perception, the IT application on SMSOs financial processes is important but not crucial to the firm s strategic advantage. The analyses done allowed two other important observations to be drawn: d) The organization structures of the analyzed firms were appropriated to the IT items they had; e) There are differences in the views of managers and employers. The conclusion of this paper, that answers its general objective is that in the managers view IT has a positive impact as an element of improvement to the firm s financial procedures, but it is not the crucial factor, nevertheless, to determine the strategic advantage of the organizations: there are other aspects that must be considered, and it is necessary the construction of complex systems that embrace other areas in the organization.